2002
DOI: 10.1080/10349120120115352
|View full text |Cite
|
Sign up to set email alerts
|

Using a Problem-Solving Approach to Teach Classroom Skills to a Student with Moderate Intellectual Disabilities within Regular Classroom Settings

Abstract: We examined the use of a problem-solving intervention to teach classroom skills to a student with moderate intellectual disabilities. She was receiving her education in regular classrooms at her local primary school. The student was taught the targeted skills in a resource room removed from the regular classroom. She successfully generalised the skills to regular classrooms. The problem-solving intervention was evaluated using a multiple baseline design across classrooms. Regular classroom teachers indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…• Teach students to decode situations and make decisions regarding actions needed to improve behaviors that support academic performance (e.g., asking for assistance, completing an assignment; O'Reilly, Lancioni, Gardiner, Tiernan, & Lacy, 2002).…”
Section: Decision Makingmentioning
confidence: 99%
“…• Teach students to decode situations and make decisions regarding actions needed to improve behaviors that support academic performance (e.g., asking for assistance, completing an assignment; O'Reilly, Lancioni, Gardiner, Tiernan, & Lacy, 2002).…”
Section: Decision Makingmentioning
confidence: 99%
“…Problem-solving research with individuals with disabilities focused on solving problems related to transition goals and self-determination (Agran et al, 2000), home and school (Cote et al, 2010), social situations (O'Reilly, Lancioni, Gardiner, Tiernan, & Lacy, 2002), and vocational and daily functioning (Bambara & Gomez, 2001). Furthermore, studies used various interventions.…”
mentioning
confidence: 98%
“…Although not specific to students with ASD, literature examining problem-solving instruction for students with disabilities suggests these individuals can learn to problem-solve (Agran, Blanchard, & Wehmeyer, 2000; Cote et al, 2010). Problem-solving research with individuals with disabilities focused on solving problems related to transition goals and self-determination (Agran et al, 2000), home and school (Cote et al, 2010), social situations (O’Reilly, Lancioni, Gardiner, Tiernan, & Lacy, 2002), and vocational and daily functioning (Bambara & Gomez, 2001). Furthermore, studies used various interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Social problem-solving interventions have successfully been used to teach social skills to a variety of populations, including individuals with intellectual disabilities and traumatic brain injuries (e.g., Foxx, Martella, & Marchand-Martella, 1989;O'Reilly, Lancioni, Gardiner, Tiernan, & Lacey, 2002;O'Reilly, Lancioni & O'Kane, 2000). These interventions have produced very robust outcomes, with social skills generalizing across regular school settings and vocational settings (e.g., Foxx, Faw, & Weber, 1991;O'Reilly & Chasdey-Rusch, 1992;O'Reilly et al, 2002). Additionally, several studies have demonstrated that such interventions can produce longterm positive changes in social behavior (Foxx & Faw, 1992;O'Reilly, Lancioni, & Kierans, 2000).…”
mentioning
confidence: 99%